2020
DOI: 10.1002/jac5.1339
|View full text |Cite
|
Sign up to set email alerts
|

Pursuing postgraduate pharmacy training in the United States for international pharmacy graduates: Approaches, current status, challenges, and future perspectives

Abstract: AimsThis paper aims to describe the procedures and current status regarding the pursuit of postgraduate pharmacy training in the United States for international pharmacy graduates. Also, it highlights some of the challenges those individuals may face throughout their journey and provides future perspectives.MethodsTo describe the procedures regarding the pursuit of postgraduate pharmacy training in the United States, we searched and summarized the information in public online platforms, such as the National Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Although the growth of pharmacy residency and graduate pharmacy programs has been noticeable, less attention has been given to pharmacy fellowship programs, which have a great emphasis on research. Research fellowship programs were originally developed in the United States, where many Saudi pharmacists obtained their postgraduate training, including completing fellowship training [23]. As only one pharmacy fellowship program is available in Saudi Arabia, it is suggested that well-established pharmacy colleges develop and promote research fellowship programs (clinical or laboratory-based) to further enhance the multidimensional research skills of pharmacists who would work in clinical, research, or industrial settings.…”
Section: Discussionmentioning
confidence: 99%
“…Although the growth of pharmacy residency and graduate pharmacy programs has been noticeable, less attention has been given to pharmacy fellowship programs, which have a great emphasis on research. Research fellowship programs were originally developed in the United States, where many Saudi pharmacists obtained their postgraduate training, including completing fellowship training [23]. As only one pharmacy fellowship program is available in Saudi Arabia, it is suggested that well-established pharmacy colleges develop and promote research fellowship programs (clinical or laboratory-based) to further enhance the multidimensional research skills of pharmacists who would work in clinical, research, or industrial settings.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, healthcare policymakers should consider investing heavily in additional logistic, financial, and social support for individuals interested in establishing cardiology training sites in these underserved areas. Another solution to this challenge is to increase the number of individuals obtaining their cardiology training in the United States to meet the current demand 27 …”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Additionally, healthcare policymakers should consider investing heavily in additional logistic, financial, and social support for individuals interested in establishing cardiology training sites in these underserved areas. Another solution to this challenge is to increase the number of individuals obtaining their cardiology training in the United States to meet the current demand 27. Moreover, there is an excellent opportunity to explore activating telehealth in rural areas that lack pharmacist-run cardiology clinics where pharmacists could run virtual clinics and provide patient care to those in need.…”
mentioning
confidence: 99%
“…Currently, there are more than 20 colleges of pharmacy across KSA that offer Doctor of Pharmacy (PharmD) degree programs. In fact, the vast majority of clinical pharmacy leaders and advocates in KSA have been trained in the US, where they have completed general and specialized clinical pharmacy residencies, and many have completed research fellowships ( Badreldin et al, 2021 ).…”
Section: History Of Clinical Pharmacy In Ksamentioning
confidence: 99%
“…The US has several pharmacy fellowship programs specialized in ID to prepare pharmacists to become independent researchers ( Badreldin et al, 2021 , Korayem et al, 2021 ). Pharmacy fellowship programs specialized in ID have not yet been established in KSA.…”
Section: Infectious Diseases Pharmacy In Researchmentioning
confidence: 99%